1993
DOI: 10.1016/0167-6687(93)91081-5
|View full text |Cite
|
Sign up to set email alerts
|

Scale economies and performance in the French insurance industry

Abstract: The purpose of this paper is to provide for both life and non life insurance a measurement of economies of scale and an assessment of productive performance of French companies. We use a translog cost function to check the presence of scale economies and a parametric approach to construct our yardstick of productive efficiency. Our panel data covers 84 life and 243 non life companies for the period 1984-89. The main findings indicate both the existence of increasing returns to scale and a wide dispersion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…We observe that for all size classes, market factors only explain a small fraction of the large cost differences (upper panel). Accordingly, the TFA estimates suggest that X-inefficiency is large: the overall inefficiency residual 13 Suret (1991) reports economies of scale for the Canadian property and casualty insurance industry, whereas Fecher, Perelman, and Pestieau (1991) find modest economies of scale in the French nonlife industry of 4 percent. Hirao and Inoue (2004) examine the Japanese nonlife insurance industry and find significant economies of scale for Japanese insurers.…”
Section: Scale Economies and X-efficiencymentioning
confidence: 99%
“…We observe that for all size classes, market factors only explain a small fraction of the large cost differences (upper panel). Accordingly, the TFA estimates suggest that X-inefficiency is large: the overall inefficiency residual 13 Suret (1991) reports economies of scale for the Canadian property and casualty insurance industry, whereas Fecher, Perelman, and Pestieau (1991) find modest economies of scale in the French nonlife industry of 4 percent. Hirao and Inoue (2004) examine the Japanese nonlife insurance industry and find significant economies of scale for Japanese insurers.…”
Section: Scale Economies and X-efficiencymentioning
confidence: 99%
“…These loss-prevention costs would be embedded in the expense component of the premium rate. For these reason and to facilitate comparison with prior work, recent studies by Fields and Murphy (1989), Eisen (1991), Kaye (1991), Fecher, Perelman, andPesticau (1991), Sigma (4/91 pp. 1-20) and this paper use premiums as the measure of insurer output.…”
Section: Methodsmentioning
confidence: 99%
“…However, this will not be the case if small firms find a niche by differentiating their product. Fecher, Perelman and Pesticau (1991) suggest that reinsurance might be used as a measure of the cost of equity. Reinsurance involves the sale of premium for future coverage.…”
Section: Functional Formmentioning
confidence: 99%
“…A lot of studies have tried to establish a link between size and performance; however, most of them have shown that large companies are on average more efficient than small companies. This is due to the market power of large companies, strategic grouping by companies, and economies of scale (Dhawan, 2001 (Nemoto & Asai, 2002;Symeou, 2011), insurance (Fecher, Perelman, & Pestieau, 1993), transport (Assaf, 2009;Assaf & Gillen, 2012) and hotels (Assaf, Barros, & Josiassen, 2012;Pulina, Detotto, & Paba, 2010). With regard to the ski industry, the study carried out by Falk (2009) compared the efficiency of large ski resort conglomerates with independent ski resorts.…”
Section: Hypotheses Developmentmentioning
confidence: 99%